Achieving Pregnancy Using Primary Care Interventions to Identify the Fertile Window - Bouchard, Thomas P.; Fehring, Richard J.; Schneider, Mary M. (Frontiers in Medicine, 2018)
Objective To determine the effectiveness of achieving pregnancy with focused intercourse in the fertile window identified using natural fertility indicators. Methods 24-cycle prospective effectiveness study. Setting A North American web-based fertility monitoring service. Participants 256 North American women aged 20–43 (mean age 29.2 years) seeking to achieve pregnancy. Intervention Participants identified their fertile window with either electronic hormonal fertility monitoring or cervical mucus monitoring, or both, and recorded their observations on an online fertility tracking system. Main outcome measures Pregnancies were validated by nurses with an online self-assessed pregnancy evaluation form. Survival analysis was used to determine pregnancy rates. Results There were 150 pregnancies among the 256 participants with an overall pregnancy rate of 78 per 100 women over 12 menstrual cycles. There were 54 pregnancies (68%) among the 80 women using the fertility monitor, 11 pregnancies (46%) among the 24 women using mucus monitoring, and 90 (63%) among the 143 women using both mucus and monitor. The 12-cycle pregnancy rates per 100 women were 83 (monitor group), 72 (mucus group), and 75 (mucus and monitor group). Pregnancy rates reached 100% at 24 cycles of use for those women using the hormonal fertility monitor. Conclusion Use of the hormonal fertility monitor alone seems to offer the best natural estimate of the fertile phase of the menstrual cycle for women wishing to achieve a pregnancy. Focusing intercourse through 24 menstrual cycles can be beneficial for achieving pregnancy.